Diet, body composition, and bone mass in well-trained cyclists - Santos da Rocha Penteado, V.; Heldan de Moura Castro, C.; de Medeiros Pinheiro, M.; Santana, M.; Bertolino, S.; Tulio de Mello, M.; Szejnfeld, V. L. (Journal of Clinical Densitometry, 2009)
Cycling is believed to be associated with low bone mass. In this study, we investigate food intake, body composition, and bone mass in well-trained young adult cyclists compared with those in sedentary controls. Four-day estimated diet records were used to study dietary intake in 31 cyclists and 28 sedentary controls (all male, 24 yr old on average), together with maximal oxygen uptake (VO2max), body composition, and bone mass measurements (dual-energy X-ray absorptiometry). The VO2max values were twice as high as those in the cyclists, whereas no significant difference in bone mass was observed between cyclists and controls. A total of 10 cyclists and 9 controls had low bone mass. Total-body lean mass and appendicular skeletal muscle mass were higher in cyclists (p < 0.001), whereas percentage of body fat was lower (p < 0.001) compared with that of the controls. Energy and macro- and micronutrient intake was higher in the cyclists than in the controls (p < 0.01). Energy consumption was considered adequate in the cyclists, whereas lipid and protein intake was higher than the American College of Sports Medicine recommendation. Lipid consumption negatively correlated with bone mass in the athletes. Our results demonstrate that cycling was associated with greater aerobic conditioning and lean mass without significant association with bone mass compared with sedentary controls.